The serodiagnositic value of Chlamydia trachomatis antigens in antibody detection using luciferase immunosorbent assay - Pang, Yulian; Shui, Jingwei; Li, Changchang; Li, Yongzhi; Chen, Hongliang; Tang, Shixing (Frontiers in Public Health, 2024)
Among the different antigens used in the detection of anti-C. trachomatis antibodies, significant differences in sensitivity and specificity have been observed. Further evaluation of C. trachomatis antigens in antibody detection is urgently needed for the development and application of C. trachomatis serologic assays. C. trachomatis antigens Pgp3, TmeA, InaC and HSP60 were selected and used in luciferase immunosorbent assay (LISA). The detection results obtained from well-defined C. trachomatis positive and negative samples were compared with the commercial C. trachomatis ELISA (Mikrogen) for performance evaluation. Pgp3, TmeA, InaC and HSP60-based LISA showed sensitivity of 92.8%, 88.8%, 90.4% and 94.4%, and specificity of 99.2%, 99.2%, 99.2% and 92%, respectively. ROC analysis indicated that Pgp3-based LISA showed similar performance to Mikrogen ELISA (AUC 0.986 vs 0.993, P = 0.207). Furthermore, four C. trachomatis antigens achieved strong diagnostic efficiency, i.e. positive-likelihood ratios [+LR] ≥ 10 in C. trachomatis-infected women and negative-likelihood ratios [-LR] ≤ 0.1 in C. trachomatis negative low exposure risk children, but only Pgp3 and TmeA showed strong diagnostic value in general adults. In addition, Pgp3, TmeA and InaC, but not HSP60, achieved high performance, i.e. both positive predictive value [PPV] and negative predictive value [NPV] ≥ 90.9%, and showed no significant cross-reactivity with anti-C. pneumoniae. Three C. trachomatis species-specific antigens Pgp3, TmeA, and InaC show superior performance in the detection of anti-C. trachomatis antibody, indicating the potential to be used in developing C. trachomatis serologic tests.